Study on Exchange of Radioactive Bromide Ion on Duolite A-162 Resin - Lokhande, R.S.; Karthikeyan, Pretty (Asian Journal of Chemistry, 2010)
The kinetics of ion exchange reaction has been studied by the application of 82Br as tracer isotope. The exchange rates of ion exchange resin Duolite A-162 have been determined. Kinetics of ion exchange at different temperatures ranging from 27 to 50ºC and particularly at low concentration of electrolyte (KBr) ranging from 0.0005 M to 0.1 M and for different amount of ion exchange resin ranging from 1.0 g to 5.0 g has been carried out.